INOVASI DAN DIVERSIFIKASI DANGKE SEBAGAI PANGAN LOKAL UNGGULAN BERBASIS PENGEMBANGAN EKONOMI KREATIF HULU-HILIR DI KELURAHAN MATARAN KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Ahmad Amir -; Samintang; Fakhiratunnisa Putri Oceani; Fadhilah Isnaeni; Munawwara Ildana; Marini Amalia Mansur; Sri Ulfa; Sarniati; Akbar Waddu; Abd. Gafur; Hartawan Ansar; Zalva Nur Afifah Tamsil; Salman Iskandar; Muh. Alfan Asmari; Muh Figri; Usman (LP2M Universitas Hasanuddin, 2023)
Dangke is one of the prima donna local foods typical of Enrekang Regency. However, as times progressed, breeders faced many obstacles, especially in Mataran Village, Anggeraja District, and Enrekang Regency. This is motivated by the management of livestock pens that have not been optimal, product diversification that has not been maximized, the lack of penetration of digital marketing-based marketing and financial records for Micro, Small, and Medium Enterprises, and the lack of close multi-sectoral collaboration with relevant stakeholders. Therefore, a massive and sustainable community empowerment program is needed for farmer groups, Farmer Business Groups (KUT), Housewives/PKK, and Youth Organizations in Mataran Village as a real effort to improve the community economy based on the creative economy from upstream to downstream. This service activity was carried out for approximately six months in Mataran Village with a blended system (offline and online). This community service activity concludes that the